Ability for Autothermal process of low-temperature pyrolysis of peat; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh; he 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh[proceedings] - Suglobova N. V.; Plakhova T. M. Tatiana Mikhailovna; Kazakov A. V. Aleksandr Vladimirovich; Zavorin A. S. Aleksandr Sergeevich (Power System and Renewable Energy, 2014)
Title screen